Effect of hydrogen bond interaction on protein phase transition - Leong, Hon Wai (2013)
We derive the grand partition function of protein chain by restricting dihedral angles to exist only in five distinct states and assume that the dominant noncovalent potential is the hydrogen bond interaction. We investigate the phase transition of protein secondary structures and the order of the transition through analyzing its heat capacity. Our theory demonstrates the presence of α-β-coil structural phase transition in the protein polyalanine.